URGENSI KAJIAN FIQH AL-BI’AH DALAM PEMENUHAN URUSAN KONKUREN BIDANG PELAYANAN KEBERSIHAN DI KABUPATEN LUWU TIMUR - Syafaat Anugrah Pradana (Gorontalo Law Review, 2022)
This study aims to find out and analyze the role and efforts of the East Luwu Regency government in tackling waste in terms of the analysis of Fiqh Al-Bi'ah. The type of research used is normative-empirical legal research using a socio-legal approach. The location of the study was carried out at the East Luwu Regency Environmental Agency. The results of the study illustrate that in general, people who often throw garbage into the lake are caused by the lack of facilities from the government such as the provision of garbage bins. In addition, the Environmental Agency's program in the procurement of garbage bin vehicles was programmed in 2018 but until 2020, the program has not been evenly distributed to all districts in East Luwu Regency. Some indicators that cause cleaning services to experience obstacles in East Luwu Regency such as limited budgets of local governments and people who still tend to have no awareness of environmental cleanliness. The call to always protect the environment from the scholars (fiqh al-bi'ah) is needed in increasing public awareness in maintaining cleanliness.